The Role of Stakeholders in Infrastructure Development that supports the Higher Education Innovation Ecosystem in Indonesia - Taufiq Dwi Tamtomo; Ayomi Dita Rarasati; Achmad Jaka Santos Adiwijaya (Journal of International Conference Proceedings (JICP), 2019)
Higher education plays a role as a driver of economic growth through the development of science and technology transfer. Many studies explain the factors that influence the achievement of economic growth are human knowledge, which is generally known as a Knowledge Economy (Knowledge-Based Economy) where Human and Resources are important assets. Universities function to develop knowledge so that they are able to produce innovative and competitive human resources. based on the current Global Competitiveness Index report Indonesia's competitiveness in the innovation pillar is ranked 31 in 2017.